2010
DOI: 10.1152/japplphysiol.00285.2009
|View full text |Cite
|
Sign up to set email alerts
|

Nasal nitric oxide and regulation of human pulmonary blood flow in the upright position

Abstract: There are a number of evidences suggesting that lung perfusion distribution is under active regulation and determined by several factors in addition to gravity. In this work, we hypothesised that autoinhalation of nitric oxide (NO), produced in the human nasal airways, may be one important factor regulating human lung perfusion distribution in the upright position. In 15 healthy volunteers, we used single-photon emission computed tomography technique and two tracers (99mTc and 113mIn) labeled with human macroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 143 publications
(224 reference statements)
0
5
0
Order By: Relevance
“…In prone posture, on the other hand, no change in blood flow distribution was seen after NO synthase inhibition. 51 Later, in a study by Sánchez-Crespo et al, 53 NO produced in the upper airways was also confirmed to have a significant influence on the distribution of lung blood flow.…”
Section: Distribution Of Regional Lung Perfusion At Normal Gravitymentioning
confidence: 89%
“…In prone posture, on the other hand, no change in blood flow distribution was seen after NO synthase inhibition. 51 Later, in a study by Sánchez-Crespo et al, 53 NO produced in the upper airways was also confirmed to have a significant influence on the distribution of lung blood flow.…”
Section: Distribution Of Regional Lung Perfusion At Normal Gravitymentioning
confidence: 89%
“…It is functionally equipped to humidify, warm, and filter inspired air ( Walker et al, 2016 ). It also increases nitric oxide production in the airway, and has positive effects upon pulmonary perfusion ( Sanchez Crespo et al, 2010 ), head posture ( Sabatucci et al, 2015 ), and cognitive function ( Zelano et al, 2016 ). Mouth breathing is more common during exercise and for those with nasal breathing difficulties ( Niinimaa, 1983 ).…”
Section: Breath Toolsmentioning
confidence: 99%
“…With an adaptation period, nasal breathing during exercise may cause reduced BR, reduced hypocapnia, and increased nitric oxide production ( Dallam et al, 2018 ). Nitric oxide production is itself beneficial as a vasodilator and bronchodilator ( Sanchez Crespo et al, 2010 ; Thornadtsson et al, 2017 ), perhaps reducing the risk for flow limitation. While nasal breathing utilizes a smaller airway, which is a limitation at higher exercise intensities, it appears to increase diaphragmatic function ( Trevisan et al, 2015 ), which could be a long-term advantage (see section “Deep”).…”
Section: Breath Toolsmentioning
confidence: 99%
“…Articles were excluded if they reported on exogenous (supplementary) NO inhalation, if they studied exhaled NO as a tool for assessing airway inflammation, or if nasal breathing was studied in combination with other breathing interventions (e.g., deep/slow breathing). Using single photon emission computed tomography during separate bouts of upright nasal or oral breathing in healthy adults, Crespo et al (2010) found that nasal breathing elicited blood flow redistribution from caudal and dorsal regions of the lung to the less-perfused cranial and ventral regions. For the poorly perfused lung regions, such as the apical region, this represented a 24% increase in blood flow.…”
Section: Literaturementioning
confidence: 99%
“…Others suggest that nasal breathing might attenuate pulmonary hypertension by vasodilating the pulmonary vasculature (Settergren et al 1998). Although exogenous (supplementary) NO is known to reduce vascular resistance and increase pulmonary blood flow in healthy and patient populations (Settergren et al 1998;Crespo et al 2010), the concentration of endogenous (nasally-derived) NO is considerably lower than the concentrations used in NO-enriched air (Törnberg et al 2002). Therefore, an important consideration is whether increased NO uptake via nasal breathing exerts meaningful effects in healthy or patient populations.…”
Section: Premise and Plausibilitymentioning
confidence: 99%